Analysis of Torsional Vibration of Diesel Shaft System using Hard Coupling with Working Machine - Le, Cao Hieu; Nguyen, Van Tinh; Le, Van Cuong (Tập san Khoa học và kỹ thuật trường Đại học Bình Dương, 2023)
The model is built to analyze and calculate the torsional vibration of the internal combustion engine shaft system and the generator connected by hard coupling to assess the response to the free and forced vibration of the shaft system, thereby serving as a basis for devising a suitable plan to reduce or avoid the problem of shaft torsion vibration. The results of the research include: modeling and building a separate calculation program for shaft torsion vibrations using MATLAB software; free vibration response analysis including calculating the vibration mode frequency and corresponding vibration forms; analyzing the forced vibration response including the amplitude of vibration of the degrees of freedom and the torsion stress of each element.